(untitled) ("Conference on Universal Science Research 2023", 2024)
This thesis explores idiomatic expressions in English and Uzbek, conducting a contrastive analysis to highlight linguistic, cultural, and structural differences between the two languages. Idioms often pose challenges for translators due to their figurative meanings, which may not align with direct word-for-word translations. This research identifies common idiomatic expressions in both languages, analyzes their syntactic and semantic properties, and examines the translation strategies used to overcome cultural and linguistic barriers. The study also addresses the implications of these strategies for language learners, emphasizing the need for cultural competence alongside linguistic proficiency in translation.